The Earle Birney – Malcolm Lowry Connection. - Foxcroft, Nigel H.; Høgsbjerg, Christian (University of Toronto Quarterly, 2022)
The eminent Canadian poet, Earle Birney (1904–95), and the late modernist writer, Malcolm Lowry (1909–57), shared not only a supportive friendship in Vancouver (ignited by Sybil Hutchinson in 1947) involving the patronage of each other's verses. Their deeper connections were rooted in shared experiences under the influence of Marxist ideas in 1930s England. A self-proclaimed "working-class boy," Birney was radicalized toward Marxism whilst studying for a Toronto doctoral degree during the Great Depression. Attracted to the Young Communist League, he was won over to Trotskyism in 1933 by Kenneth and Sylvia Johnstone. Convinced that the Communist position was "basically unMarxist" for failing to build a united front against Adolf Hitler, he co-launched a branch of the International Left Opposition (Trotskyist) of Canada and organized political groups in Utah. Yet it was in the United Kingdom in 1934 that he joined (with Esther Heiger, C.L.R. James, and others) the Marxist group within the Independent Labour Party. His correspondence with Trotsky culminated in a visit to Norway to seek advice. His doctoral thesis, 1930s criticism, and literary works – such as Down the Long Table – were shaped by Marxist aesthetics. A Cambridge undergraduate in English in 1929–32, Lowry was aware of the appeal of Marxism to many UK intellectuals. He became involved in political debates hosted by the Haldanes at Roebuck House and contributed to The Venture and Experiment. Liaising with the "Cambridge Five," he was impressed by Guy Burgess who lent his surname to a character in his 1930s novel, In Ballast to the White Sea (2014), a treatise on communism and revolutions of politics and the soul. Inspired by Waldo Frank, he ensured that Trotskyism and its impact on Mexico are central themes in Under the Volcano (1947).